ENHANCING STUDENTS’ LEARNING OUTCOMES USING PROJECT-BASED LEARNING IN DYNAMIC ELECTRICITY - Adha, Al Fajri; Syefrinando, Boby; Sulman, Fauzan (Physics and Science Education Journal (PSEJ), 2025)
This study aims to improve students’ learning outcomes through the implementation of the Project-Based Learning (PjBL) model in Dynamic Electricity for Grade XII MIPA students at SMAN 13 Bungo. The research employed a classroom action research design conducted in two cycles, with each cycle consisting of two meetings and encompassing four stages: planning, action implementation, observation and evaluation, and reflection. The research subjects were 33 students of Grade XII MIPA at SMAN 13 Bungo, comprising 19 male and 14 female students. Data were analyzed using both qualitative and quantitative techniques. The results indicate that the Project-Based Learning (PjBL) model is effective in improving students’ learning outcomes in Dynamic Electricity. Based on observation data and end-of-cycle assessments in the form of essay tests, Cycle I resulted in an average score of 69.2, with 10 students achieving mastery, representing a mastery percentage of 30.3%. In Cycle II, the average score increased to 82.2, with 29 students achieving mastery, corresponding to a mastery percentage of 87.9%. In addition, both student activity and teacher performance showed noticeable improvement throughout the learning process. Therefore, it can be concluded that the Project-Based Learning model is effective and successful in enhancing students’ learning outcomes in Dynamic Electricity